OPTIMALISASI PEMANFAATAN POTENSI LOKAL DAN SOSIALISASI KOPERASI MERAH PUTIH UNTUK MENINGKATKAN EFISIENSI, TRANSPARANSI MENINGKATKAN KEMANDIRIAN EKONOMI DESA - Jaenab Jaenab; Nurul Huda; Al Qomar; Karina Karina; Raihan Al Farizin; Nur Ayuningsih (Jurnal Padamu Negeri, 2025)
This socialization seminar of the Merah Putih Cooperative (KMP) was organized through a collaboration between KKN Impact students from Nipa village, Ambalawi sub-district, as the main activity of KKN Impact STIE Bima, the KKN Nipa Supervising Lecturers Team, and the Head of Nipa Village, Ambalawi sub-district, Bima Regency. The event took place in the Nipa village hall on Thursday, September 4, 2025. The implementation method consisted of 1) Preparation stage: coordination with the KKN Impact STIE Bima committee, coordination to request speakers from the Cooperative and MSME Office of Bima Regency, BPMdes Bima Regency, and speakers from STIE Bima Institution, and preparation of equipment and supplies. 2) Implementation stage: The community service resulted in the Merah Putih Cooperative seminar attended by administrators from six villages in Ambalawi sub-district, Bima Regency, held with active participation from speakers representing the Cooperative and MSME Office of Bima Regency, specifically the Head of the Savings and Loan Financing Facilities Division (FPSP) and BPMdes Bima Regency. Participants included the Ambalawi sub-district head's economic section representative, the Head of Nipa Village, the FPSP head and staff, BPMdes head and staff, Babinsa, Merah Putih cooperative managers from Ambalawi sub-district, village heads, BUMDes heads, community leaders, youth leaders, and MSME actors, totaling 32 attendees. The seminar focused on managing financing facilitation for cooperatives and MSMEs, developing cooperative institutions, supervising the savings and loan operations, and supporting village economic development through empowering cooperatives and MSMEs based on local potential. It aimed to enhance cooperative financial management capacity as an effort to strengthen institutions and optimize the cooperative's role in village economic development. Through this forum, participants were encouraged to understand the principles of transparency, accountability, and collaboration among stakeholders to realize cooperatives as inclusive, sustainable drivers of the local economy. The seminar also served as a strategic platform to support cooperative digitalization and boost cooperatives' role in promoting economic independence in village communities. 3) Evaluation stage: Group photo, reflection on activity results, and evaluation.